Science in the final years of Elementary School: a look at Physics teaching (Research, Society and Development, 2020)
This paper discusses a methodological proposal for physics teaching in the final years of elementary school.  Based on a literature review on the subject, it is observed that the teaching of sciences for the final years of elementary school prioritizes topics related to the area of Biology, with the predominance of the teacher in the area of Biological Sciences as the responsible for the discipline of sciences in the final years of elementary school.  Thus, the curricular proposal that is presented builds the teaching of sciences as an interrelationship between Physics, Chemistry and Biology, each subject being governed by an expert in each area.  Under the section of physics teaching, the teaching work developed by the regent of the discipline is described, including the choices of themes, activities and composition of didactic material for sixth and seventh year classes of elementary school.  Through action research, information was collected about the development of students in the knowledge of physics and its relationship with daily life.  With content analysis, it was possible to infer about the contribution that the experiences and discussions provided by the physical phenomena studied during the school year promoted in the view of Physics as science, in addition to its role in the formation of students in the final years of elementary school.